The lightness distribution of the red color for the nail plate related to human healthy level - We-Li Ou; Chia-Ting Li; Da-Chih Chen (Archives of Community Medicine and Public Health - Peertechz Publications, 2023)
The water content of the human nail plate may be a health indicator related to human beings. In Chinese traditional medical science, the traditional Chinese medicine physician usually examines the nail plate conditions combined with other body physical symptoms to determine the physical health level. Usually, for people with healthy bodies, the nail plates appear shining pink color. On the other hand, people get ills, their nail plates will appear in different colors except for shining pink color nail plates. The pink color nail plates have come from the red blood flowing through the body capillaries. A healthy people, the blood flow through capillaries should be very smooth. Obviously, the capillaries inside the human nail plates with a smooth flow of blood will cause the human nail plates to appear pink in color. Inspect the lightness distribution of the digital photo red color for the human nail plates only, a very clear result can be seen from the lightness distribution. The lightness distribution of the red color of the digital photo from the healthy human nail plate is wider than the lightness distribution of the digital photo from the dry nail plate.